PROSPECTING ASEAN-MERCOSUR COOPERATION: APEC 2.0, TPP 2.0, OR EXPANDED EAS? - Mulyaman, Darynaufal; Djaya, Jason Rafael Setia; Pradono, Bimo Adi (Universitas Nahdlatul Ulama Kalimantan Timur, 2023)
Association of Southeast Asian Nations or Asean is one of the regional organizations that exist in today’s world. Then, Mercosur or Mercado Común del Sur (Southern Common Market) is a South American trade bloc that moving forward beyond the traditional regional bloc, because the nature of its organization lays more on economic and trade transactions, rather than politics. As globalization grows, these two regional organizations seek more deep cooperation. Nevertheless, through a comparative historical qualitative descriptive analysis, this paper argues that the cooperation will lead to both failures and failed to secure engagement because of the nature of Spaghetti Bowls (or Noodle Bowls in Asia) in the organization country member’s respective economic crafts since the country members also join other trans-continental economic partnership. Moreover, both regional groups are naturally not the traditional partners of each other, thus How the Asean and Mercosur cooperation could benefit each other despite the nature of Spaghetti Bowls in their regionalization? Furthermore, this paper also argues that Asean could learn how the Mercosur model could be used for its AEC or Asean Economic Community since Mercosur intra-trade is more advanced than Asean intra-trade. Further, the comparison analysis also provided in this research.